THE ROLE OF INTERNATIONAL ORGANIZATION FOR MIGRATION (IOM) IN COMBATING HUMAN TRAFFICKING IN UKRAINE - Hana Yunianti (2012)
Nowadays, human trafficking issue becoming a migration challenge in the world. Practices are including debt bondage, forced labour, and sexual slavery, and more occurring in every country, particularly Ukraine. In this state, human trafficking arose and contributes negative impact for the stability in Ukraine. This thesis entitled "The Role of International Organization for Migration (IOM) in Combating Human Trafficking in Ukraine" tried to descript and give information about actions taken by